Exploring drivers of psychology well-being at music festivals - Loureiro, S. M. C. (2021)
The aim of the current study is to analyze tourist engagement with music festivals and their psychological well-being is achieved through surprise consumption, positive affect, arousal delight and satisfaction. A sample of 394 usable questionnaires allow us to understand that surprising consumption, arousal, positive affect and satisfaction are very important drivers to engage visitors to music festivals. Engaged tourists are more willing to reach a positive psychological well-being.